Pengaruh Transfer Finansial Anak terhadap Partisipasi Kerja Orang Tua Lansia di Indonesia - Kinasih, Laras Sekar; Rini, Ariska Nurfajar (Jurnal Dinamika Ekonomi Pembangunan, 2023)
Changes in the demographic structure contribute to the aging of the population. The constraints imposed by the limited formal support from the government lead to a dependency of the elderly population on intergenerational support and income derived from the labor market. This research analyze the role between financial transfers provided by adult children to elderly parents who have entered retirement to the workforce participation of the elderly in Indonesia. Utilizing secondary data from the Indonesian Family Life Survey 5 (IFLS 5), the research focuses on individuals aged 50 years or older who have entered retirement. Findings through logit regression suggest that financial transfers may diminish elderly workforce participation. Additional variables that also influencing elderly workforce participation include pension funds, age, gender, and marital status. Conversely, variables such as marital status and living with children variables do not exhibit a significant impact on elderly workforce participation.